2023
DOI: 10.1128/spectrum.04535-22
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics and Pathogenicity Analysis of a Low Virulence G2a Porcine Epidemic Diarrhea Virus

Abstract: The current epidemic of porcine epidemic diarrhea virus (PEDV) G2 has caused huge economic losses to the pig industry. Evaluation for low virulence of the PEDV strains of subgroup G2a would be useful for the future development of effective vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In our laboratory, multiple strains of PEDV, such as HB2018, HB2019, HB2020 and DY2020, were successfully isolated from intestinal content samples, with DY2020 exhibited highest virus titres [19, 22]. Although faeces, serum and rectal swabs from PEDV-positive pigs were also regarded as isolated samples by few reports [23, 24], most of the PEDV isolates were successfully retrieved from SICs [13, 21, 25–27], suggesting that PEDV-positive samples from intestinal contents may be more advantageous for PEDV isolation. The culture of PEDV relies on the trypsin-mediated cleavage of the spike (S) protein, which induces syncytium formation in vitro [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our laboratory, multiple strains of PEDV, such as HB2018, HB2019, HB2020 and DY2020, were successfully isolated from intestinal content samples, with DY2020 exhibited highest virus titres [19, 22]. Although faeces, serum and rectal swabs from PEDV-positive pigs were also regarded as isolated samples by few reports [23, 24], most of the PEDV isolates were successfully retrieved from SICs [13, 21, 25–27], suggesting that PEDV-positive samples from intestinal contents may be more advantageous for PEDV isolation. The culture of PEDV relies on the trypsin-mediated cleavage of the spike (S) protein, which induces syncytium formation in vitro [28].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic homology between the G2 variant and the classical G1 vaccine strain ranges only from 91–94 %, which may partially account for the limited efficacy of cross-protection between the two genotypes [12]. Despite the high genomic homology (96.5 –98.5 %) among G2 variants, the pathogenicity and humoral immune responses exhibited distinct difference [13] with PEDV G2a strains demonstrated better cross-protection against the heterologous PEDV challenges [14], suggesting the biological characteristics and pathogenicity of the PEDV G2a subgroup are worthy of further study for the development of effective vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses based on circulating strains of PEDV showed that all PEDV can be classified into two genotypes, GI type and GII type: (1) GI type includes classical strains of PEDV, represented by CV777 and strains that appeared before 2010; and (2) GII type includes mutant strains found after 2010. Mutations such as insertions and deletions are frequently observed in the complete genome of variant PEDV, most of which are located in spiking genes, including the antigenic epitope region ( Yu et al, 2023 ). The S-protein of PEDV is an important structural protein of coronaviruses, and is thought to encode antigenic determinants, particularly the viral neutralization epitope.…”
Section: Discussionmentioning
confidence: 99%
“…It affects pigs of all ages, with mortality, severity, and duration of the disease diminishing as age increases. Severe cases are associated with neonatal pigs, reaching up to 100% mortality and morbidity rate of 80%–100% causing serious economic losses to the pig industry worldwide ( Salamat et al ., 2021 ; Zhuang et al ., 2022 ; Yu et al ., 2023 ), necessitating the development of an effective protection strategy. Furthermore, the emergence of novel isolates and recombinant strains in Asia has led to recurrent outbreaks (Lin et al ., 2022; Orosco, 2024a ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of vaccine development, inactivated vaccine candidates based on the GIIa strain showed greater efficacy against GIIa and GIIb strains than candidates based on the GIIb strain ( Liu et al ., 2019 ). Moreover, GIIa-based vaccine candidates can provide better immunity against both heterologous and homologous PEDV challenges than GIIb candidates ( Yu et al ., 2023 ). Thus, utilizing GIIa strains could be useful in developing more effective vaccines.…”
Section: Introductionmentioning
confidence: 99%